General Dimension‐Controlled Synthesis of Hollow Carbon Embedded with Metal Singe Atoms or Core–Shell Nanoparticles for Energy Storage Applications. Issue 27 (13th August 2018) - Song, Xiaokai; Chen, Si; Guo, Linli; Sun, Yu; Li, Xiaopeng; Cao, Xin; Wang, Zhixian; Sun, Jianhua; Lin, Chao; Wang, Yong
Abstract: Metal–organic framework (MOF) derived carbonaceous nanocomposites have recently received enormous interest due to their intriguing physiochemical properties and diverse energy applications. However, there is a lack of general synthetic approaches that can achieve flexible dimension control while manipulating metal dispersion of MOF derived carbon composites. Herein, the authors present an attractive route for the growth of zeolitic imidazolate frameworks (ZIFs) with different dimensions and types of metal nodes that can be further transformed into either core–shell nanoparticles or metal single atoms. The formation of a ZIF‐8 seed layer on ZnO template is identified as the key step, enabling uniform growth of various ZIF materials (e.g., Zn/Co‐ZIF, Zn/Fe‐ZIF, and ZIF‐7) with different dimensions (1D, 2D, and 3D). Simultaneously, this approach avoids free growth of 0D MOF particles and diminishing of the ZnO template. To demonstrate the importance of dimensional control over the growth of ZIF materials for energy application, the 1D and 2D ZnO@ZIF precursors are converted into carbon nanotube and carbon nanoplate, which are decorated with Co/CoS2 nanoparticles and Fe single atoms, respectively. Two high dimensional carbon nanocomposites deliver significantly enhanced performances compared to their 0D counterparts when employed as the Li‐ion battery anode and bifunctional oxygen electrocatalyst. Abstract : A general synthetic strategy is developed to fabricate dimension and component controlled hollow carbonaceous materials by pyrolyzing ZnO@zeolitic imidazolate framework (ZIF) core–shell nanoarchitectures. The formation of a protective ZIF‐8 seed layer on ZnO is identified as the key step to form various (0D, 1D and 3D) core–shell ZIF‐relative heterostructures. The derived carbonaceous composites deliver good electrochemical performance.